Latitude as a co‐driver of human gut microbial diversity?. (13th January 2017) - Dikongué, Emma; Ségurel, Laure
Abstract : The human gut microbial diversity has been reported to be lower in industrialized populations as compared to non‐industrialized ones. Since it is also reduced in individuals with some metabolic and inflammatory diseases as compared to healthy ones, this "loss" of diversity in industrialized populations is currently considered to be a public health issue. However, little is known on the mechanisms that are causing this pattern. Is it due to differences in diet, sanitation, medication, host genetics, and/or other unidentified factors? In this review, we propose that part of this decrease in diversity is driven by latitude, as all studied industrialized countries are in higher latitudes than non‐industrialized ones, and latitude is known to correlate with species diversity. Reanalyzing available data, we find that part of the gut microbial diversity is significantly correlated with latitude, which might therefore exacerbate the effect of lifestyle. Intriguingly, the observation of a higher diversity in industrialized countries has not been replicated in other human microbiomes. Abstract : The human gut microbiome composition and diversity is influenced by many factors, including diet, hygiene practices, medication, lifestyle (industrialized or "traditional"), and the host genetic variability. We propose that latitude is also correlated with the gut microbial diversity, given that it is the case for other microorganisms.